Level of Sports Development Assessed Through the Sport Development Index in Deli Serdang Regency - Endriani, Dewi; Syamsul Gultom; Indah Verawati; Muhammad Reza Destya (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The aim of this research is to evaluate the success of local governments in development in the sports sector in terms of the availability of open space, community participation, sports resources and community fitness levels (Sport Development Index). Therefore, this research approach is evaluative research. The sampling technique uses stratified random sampling and cluster sampling. The basic characteristics of the population used include; differences in the level of progress of a region, gender differences between men and women, differences in the ages of children aged 8-13 years, teenagers aged 14-18 years and adults aged 18-41 years, while the basic clusters used are sub-district and village or sub-district areas. The research results show that the open space index is in the low category (0.170), the human resources index is in the medium category (0.551), the community participation index is in the medium category (0.582), and the fitness index is in the low category (0.477). Overall, the Sports Development Index for Deli Serdang Regency in the year was in the low category, 0.387.